University students' online information searching strategies in different search contexts - Meng‐Jung Tsai; Jyh-Chong Liang; Huei‐Tse Hou; Chin‐Chung Tsai (2012)
This study investigates the role of search context played in university students' online information searching strategies. A total of 304 university students in Taiwan were surveyed with questionnaires in which two search contexts were defined as searching for learning, and searching for daily life information. Students' online search strategies were evaluated by the "Online Information Searching Strategy Inventory" (Tsai, 2009b). The results of paired t-tests indicated that university students' online search strategies utilised for searching daily life information were significantly better than those utilised for learning activities, especially in behavioural and metacognitive strategies. This study also drew a subsample of 20 students from the participants for in-depth interviews, to explore further the reasons for these findings. We suggest that educators need to pay more attention to helping students develop online search strategies for academic activities. In addition, only female students' metacognitive strategies were significantly different between search contexts. There may be an effect of the interaction between search context and gender on students' online searching strategies. Based on the above, suggestions are provided for future design and implementation of online information searching activities.